2018
DOI: 10.1007/s00604-018-2668-y
|View full text |Cite
|
Sign up to set email alerts
|

Carbon quantum dot-based fluorometric nitrite assay by exploiting the oxidation of iron(II) to iron(III)

Abstract: The authors describe a simple and economical fluorescence method for the determination of nitrite by utilizing the fact that nitrite possesses strong oxidation in acidic solution and is capable to transform iron(II) into iron(III) ions. The latter quenches the fluorescence of carbon quantum dots (CQDs) based on the fluorescence static and dynamic quenching effect. The optimum reaction conditions and other analytical parameters are investigated to enhance the sensitivity of the method. At the excitation wavelen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…To investigate the mechanism of quenching BSA-CuAuNCs by nitrite, rstly, XPS spectra of the system with and without nitrite were measured. It was possible that the oxidation of the core of BSA-CuAuNCs led to uorescence quenching due to oxidation capacity of nitrite (Liu et al 2018b). However, Cu2p and Au4f spectrum exhibited no obvious change, and the Cu2p spectra showed no a characteristic peak at 942 eV, indicating the absence of Cu ( ), which demonstrated that the uorescence quenching was not due to the oxidation of the metal core (Fig.…”
Section: Possible Quenching Mechanismsmentioning
confidence: 99%
“…To investigate the mechanism of quenching BSA-CuAuNCs by nitrite, rstly, XPS spectra of the system with and without nitrite were measured. It was possible that the oxidation of the core of BSA-CuAuNCs led to uorescence quenching due to oxidation capacity of nitrite (Liu et al 2018b). However, Cu2p and Au4f spectrum exhibited no obvious change, and the Cu2p spectra showed no a characteristic peak at 942 eV, indicating the absence of Cu ( ), which demonstrated that the uorescence quenching was not due to the oxidation of the metal core (Fig.…”
Section: Possible Quenching Mechanismsmentioning
confidence: 99%
“…[4][5][6] Moreover, nitrite can also react with amines, proteins and other substances in the body to produce an n-nitrosamine substance in the stomach, which will lead to different cancers and severely damage the human nervous system. 7,8 Consequently, the exploring an easy method to detect the nitrite content is urgent.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, there is no need for toxic solvents, expensive equipment, sophisticated sample preparation, and expert operators. 30,31 In spite of the vast effort, there is still a lack of accurate fluorometric sensors for many essential drugs. cence sensors have higher response stability and have been used widely for the detection of various drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The fluorometric sensors based on CQDs have numerous advantages compared to the conventional detection methods such as Raman spectroscopy, electrophoresis, high-performance liquid chromatography (HPLC), and mass spectrometry. For instance, there is no need for toxic solvents, expensive equipment, sophisticated sample preparation, and expert operators. , In spite of the vast effort, there is still a lack of accurate fluorometric sensors for many essential drugs.…”
Section: Introductionmentioning
confidence: 99%